Leadership styles for employee empowerment: Malaysian retail industry - Islam, Md Asadul; Jantan, Amer Hamzah; Rahman, Md Adnan; A. Hamid, Abu Bakar; Mahmud, Fariha; Hoque, Ashikul (Macrothink Institute, 2018)
The aim of this paper is to examine the impact of the different leadership styles on employee empowerment in the Malaysian retail industry. A quantitative study was carried out to collect and analyse the data. A survey was conducted through the convenience sampling to include one hundred respondents, who are working in retail organizations in Selangor, Malaysia. The personal data of the respondents were analysed through descriptive analysis. In addition, the inferential analysis was employed to test the hypotheses. The results of the study found that two of the three hypotheses were supported by respondents while another one was rejected. The paper includes research limitations and direction for future research.